Molecular mechanism of aberrant decidualization in adenomyosis leading to reduced endometrial receptivity - Dai, Yuanquan; Yuan, Zheng; Fan, Weisen; Lin, Zhiheng (Frontiers in Endocrinology, 2025)
Patients with adenomyosis not only experience a decrease in quality of life as a result of dysmenorrhea and severe monthly flow but they are also rendered infertile. Pregnancy rates are still low among women with adenomyosis, even with assisted reproduction. According to the current study, endometrial receptivity is primarily responsible for the lower conception rate among patients with adenomyosis. Decidualization of endometrial stromal cells is the fundamental requirement for endometrial receptivity and the maintenance of a normal pregnancy, even though endometrial receptivity is made up of a variety of cells, including immune cells, endometrial epithelial cells, and endometrial stromal cells. Our overview reveals that endometriosis deficiencies are present in patients with adenomyosis. These flaws may be linked to aberrant pathways in endometrial stromal cells, such as PI3K/Akt, JAK2/STAT3, and hedgehog. Correcting the abnormal expression of molecules in endometrial stromal cells in the endometrium of patients with adenomyosis may become the focus of research to improve endometrial receptivity and increase the pregnancy rate.